Principal Leadership Patterns in Collaborating With School Committee - Mohamad Iwan Fitriani; Mohammad Viktor Farid Hakim (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2021)
The purpose of this study was to get deeply information of leadership pattern from the headmaster in MIN Karang Baru in making cooperation and collaboration with the school committee. The approach research used qualitative with phenomenology method. The technique of collecting data used interviews and observation. Participants of the study were the headmaster, teacher, and school committee. The technique of data analysis contains three steps, namely reduction of data, data display, and taking conclusion. Meanwhile, the validity of data checking consists of credibility, transferability, dependability, and confirmation. The results showed that the leadership pattern of the MIN Karang Baru headmaster in collaboration with the school committee was very good because it was able to take advantage of the school committee's function. From the leadership orientation, the Yukl concept consists of four that are relevant to the function of the school committee, namely the orientation of the principal's duties relevant to the agent giving consideration from the school committee. Meanwhile, the school committee as an agent of support is shown in the orientation of relationship and change attitudes. Meanwhile, the school committee as a controlling agent is seen in the utilization of external factors.